Ask your own question, for FREE!
Mathematics
Gabe12704:

Simplify m - {n - [p + (m + n - p)]}

mhanifa:

Do you know where to start?

Gabe12704:

Sort of

mhanifa:

Open parenthesis one by one, start from the inner one

Gabe12704:

k

mhanifa:

Let me know what you get

Gabe12704:

2m?

mhanifa:

m - {n - [p + (m + n - p)]} = m - {n - [p + m + n - p]} = m - {n - [m + n] } = m - {n - m - n} = m - {-m} = m + m = 2m Correct

Can't find your answer? Make a FREE account and ask your own questions, OR help others and earn volunteer hours!

Join our real-time social learning platform and learn together with your friends!
Can't find your answer? Make a FREE account and ask your own questions, OR help others and earn volunteer hours!

Join our real-time social learning platform and learn together with your friends!